Antimicrobial Activity of Psidium Guajava and Piper Betle Extracts on Selected Foodborne Bacteria - Francis Parillon, Henie Edward (2006)
Five plants, namely Psidium guajava (guava), Illicium verum (star anise), Annona squamosa (sugar apple) and two cultivars of Piper betle Linn. (betel leaf), were screened for antimicrobial activity against sixteen foodborne bacteria using the agar disc diffusion method. The plants were selected on the basis of folklore medicinal reports and as practiced by people in Malaysia and the Caribbean. The methanolic extracts of all plants used in preliminary screening had antibacterial activity against at least on one bacterium with guava and the red vein (rv) and green vein (gv)cultivars of Piper betle L., demonstrating greater antimicrobial activity. I. verum extract was effective against Aeromonas hydrophila and Citrobacter freundii while the Annona squamosa extract was effective only against Vibrio parahaemolyticus. The sequentially extracted crude material from the leaves of P. betle L. (rv), P. betle L. (gv), and guava were evaluated for effectiveness against the bacteria. The methanolic extract of P. betle L. (gv) was found to be effective against both Gram-positive and Gram-negative pathogens while the methanolic extract of guava was mainly effective against the Gram-positive bacteria. The hexane and ammoniacal chloroform extracts of P. betle L. (rv) inhibited the growth of most Gram-negative pathogens.The minimum inhibitory concentration (MIC) of the methanolic extracts of P. betle L. (gv) (PBME) and guava (GME) against Kocuria rhizophila, Staphylococcus aureus, A. hydrophila, Escherichia coli O157:H7, Salmonella Typhimurium and Listeria monocytogenes and V. parahaemolyticus was investigated. The bacteria most sensitive to the GME (MIC = 1 mg/ml) were S. aureus, K. rhizophila and E. coli O157:H7 while S. aureus was the most sensitive to the PBME at the same concentration. A. hydrophila and V. parahaemolyticus were more resistant to the PBME with an MIC of 10 mg/ml. The extracts were also investigated for their killing kinetics against four bacteria. The GME completely inhibited the growth of K. rhizophila in 12 h at a concentration of 1 mg/ml while at 5 mg/ml, complete inhibition was obtained in 4 h. PBME also killed all the bacterial cells of L. monocytogenes, at a concentration of 1 mg/ml in 32 h while at 5 mg/ml, complete inhibition was obtained in 4 h. At the concentration of 1 mg/ml the rate of killing of the GME was faster than that of the PBME for all the bacteria studied.The effect on cell viability and cellular leakage of K. rhizophila, S. Typhimurium,L. monocytogenes and E. coli O157:H7 was measured after exposure to PBME and GME at a concentration of 5000 ppm (5 mg/ml). Assay of filtrates of all treated cell suspensions revealed a significantly higher (P≤0.05) release of nuclear material, K+ ions and protein than that of untreated controls, thereby indicating disruptive action on the cytoplasmic membrane of bacterial cells. The PBME caused a higher leakage of K+ ions than the GME for all the bacteria tested while total protein released by K. rhizophila and S. Typhimurium was also higher in cells treated with PBME than with GME. The PBME caused a noticeably higher (P≤0.05) release of nuclear material in the Gram-positive organisms while the GME caused a higher release in the Gram-negative. While GME caused a higher release of 260nm-absorbing materials than PBME for all the organisms investigated, both extracts appeared to have disrupted the integrity of the lipopolysaccharide (LPS) layer of the Gram-negative microorganisms. Several mechanisms of action may be involved in the growth inhibition of bacteria.The loss of cell viability and leakage of intracellular constituents observed in this study suggests that membrane damage was a major cause of lethal effect for any of the extracts.